THE FEATURES OF THE PSYCHOLOGICAL PREPARATION PROCESS OF TURON FIGHTERS TO COMPETITIONS - Salimovich, Shukurov Rahim; Sharipovna, Yusupova Zulfizar; Sharipovna, Akramova Gulhayo (International Journal of Psychosocial Rehabilitation, 2020)
This article deals with the features and advantages of the psychological preparation process in the forthcoming competition in the field of physical training, general and special psychological training of the participants of the single fighting..